Analisis Bibliometrik Penelitian Abnormal Return dan Event Study pada Pasar Saham Syariah - Fetty Nur Rahmayanti; Nurul Huda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to map and evaluate the development of research on abnormal return and event study in the Islamic stock market using a bibliometric approach. Bibliographic data were collected from Google Scholar through Publish or Perish (PoP) software version 8.17.4863.9118, covering publications from 2020 to 2025, resulting in 350 relevant journal articles. The data were analyzed using VOSviewer version 1.6.20 to identify publication trends, author collaboration networks, and keyword co-occurrence patterns. The results reveal a significant increase in research output, particularly in the post-pandemic period, indicating growing academic interest in Islamic capital markets. The dominant research themes focus on market reaction, Islamic stock indices, and event study methodologies, while author collaboration remains relatively limited and regionally clustered. Furthermore, keyword analysis highlights emerging research directions, including the integration of environmental, social, and governance (ESG) aspects, as well as risk and volatility analysis in the context of Shariah-compliant stocks. This study contributes to the literature by providing a comprehensive overview of the intellectual structure and evolution of abnormal return and event study research in Islamic stock markets. The findings are expected to serve as a reference for future academic research and to support policymakers and practitioners in developing evidence-based strategies for the Islamic capital market.